2017
DOI: 10.1111/aos.13564
|View full text |Cite
|
Sign up to set email alerts
|

Influence of exercise on the structure of the anterior chamber of the eye

Abstract: PurposeTo measure changes in anterior chamber structure before and after exercise in healthy individuals using anterior segment optical coherence tomography (ASOCT).MethodsThirty‐two healthy young individuals performed jogging for 20 min. Eye blinking rate was recorded during rest and exercise. The anterior chamber angle (ACA), angle opening distance at 500 μm from the scleral spur (AOD500), trabecular‐iris space area at 500 μm from the scleral spur (TISA500), iris concavity (IC), iris concavity ratio (CR), ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…One myopic eye and one hyperopic eye were excluded from further image and data analysis due to the low image quality. All subjects were requested to abstain from caffeine for 3 days and from any food or beverage for at least 30 min before study participation ( Li et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…One myopic eye and one hyperopic eye were excluded from further image and data analysis due to the low image quality. All subjects were requested to abstain from caffeine for 3 days and from any food or beverage for at least 30 min before study participation ( Li et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…The effects of sports activities on glaucoma, axial length, ocular blood flow, and myopia, as well as systemic diseases, such as type 2 diabetes mellitus and hypertension, have also been investigated 1,2 . Studies have reported that physical activity has an effect on ocular parameters, such as pupil size, anterior chamber angle, and neurovascular retinal features 3–5 . Retina and optic disc structures are likely to be positively affected in athletes 6 …”
mentioning
confidence: 99%
“…1,2 Studies have reported that physical activity has an effect on ocular parameters, such as pupil size, anterior chamber angle, and neurovascular retinal features. [3][4][5] Retina and optic disc structures are likely to be positively affected in athletes. 6 Optical coherence tomography angiography is a noninvasive method that has been widely used in clinics in recent years.…”
mentioning
confidence: 99%
“…Subjects with best corrected visual acuity less than 20/20, a history of ocular disease other than refractive error, a history of ocular trauma, a history of ocular laser or surgery, a history of use of any other modalities other than single-vision spectacles for myopia control, including rigid contact lenses, multifocal soft contact lenses, orthokeratology lenses and atropine, or a history of systemic disease were excluded [ 40 ]. Furthermore, subjects were instructed to take no medicines/food affecting the circulatory system 1 month before their participation, and to receive no caffeine for at least 24 hours before the study [ 41 ].…”
Section: Methodsmentioning
confidence: 99%